HUQÍQÍY BILIMLER TIYKARÍNDA AKADEMIYALÍQ LICEY OQÍWSHÍLARÍNÍŃ PUQARALÍQ POZICIYASÍN RAWAJLANDÍRÍW - Orınbetov, N.T. (SCIENCE and SOCIETY, 2021)
This article discusses factors that help young people, especially academic lyceum students, to develop their concept of citizenship, a sense of citizenship and civic position through legal education.